2013
DOI: 10.1185/03007995.2013.813839
|View full text |Cite
|
Sign up to set email alerts
|

Mixed treatment comparison of efficacy and tolerability of biologic agents in patients with rheumatoid arthritis

Abstract: In this MTC, abatacept demonstrated similar efficacy at 6 months, a higher likelihood of achieving ACR70 response and DAS28 remission at 12 months and better tolerability relative to the combined TNFi in patients with RA who had an inadequate response to conventional DMARDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Some studies that carried out indirect comparison of the efficacy of different biologicals in RA found that the difference between infliximab and other biologicals were not statistically significant [4, 5861], which supports our results for infliximab and infliximab-biosimilar.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies that carried out indirect comparison of the efficacy of different biologicals in RA found that the difference between infliximab and other biologicals were not statistically significant [4, 5861], which supports our results for infliximab and infliximab-biosimilar.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding safety and tolerability, some of the studies found significant differences between treatments, e.g., in favor of etanercept [58] or in favor of abatacept compared to a combined group of biologicals [61]. However, these studies examined a tolerability endpoint, namely the withdrawal of therapy due to adverse events, while we examined safety in terms of the occurrence of serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Desai et al (10) (11) reported estimates favoring adalimumab for treatment discontinuations due to AEs (OR 2.00, 95% CrI 1.17-3.49), which is also consistent with our conclusion. Hochberg et al (9) combined etanercept, infliximab, and adalimumab as a single TNF inhibitor group and compared the treatment discontinuations due to AEs with abatacept. Therefore, their estimates are not directly comparable with observations from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Three prior systematic reviews conducted indirect comparisons using Bayesian methods for evaluating the comparative safety of TIMs using RCT data (9)(10)(11). The safety outcome evaluated in all 3 reviews was discontinuations due to AEs reported in RCTs of individual TIMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation